The virtual pediatric perioperative home, experience at a major metropolitan safety net hospital. Issue 6 (25th March 2021) - Conley, Christopher; Facchin, Mark; Gu, Qingrou; Mukerji, Shivali; Cohen, Robyn; O'Brien, Sharon; Nurhussien, Lina; Ferrari, Lynne
Abstract: Introduction: Successes from anesthesiologist‐led perioperative surgical homes in the adult patient population have inspired similar initiatives by pediatric hospitals. Typically the care coordination for these perioperative homes is run through hospital‐funded, on‐site, preanesthesia clinics. Preliminary data from pediatric perioperative homes have shown promising results in improved patient outcomes and decreased length of hospital stay. The majority of pediatric surgeries within the country are performed in nonpediatric hospitals. Such centers may not have the infrastructure or financial resources for a freestanding pediatric preanesthesia clinic. Faced with this situation at the largest safety net hospital in New England, the authors present their experience designing and implementing a "Virtual Pediatric Perioperative Home, " a telemedicine‐based triage and preanesthetic optimization for pediatric patients at Boston Medical Center, Boston, MA. Methods: A retrospective chart review of all pediatric anesthesia cases at Boston Medical Center from February 1, 2019, to January 31, 2020, as well as the number of pediatric cases canceled or postponed on the day of surgery for any reason during the same time period was conducted. Results: From February 1, 2019, to January 31, 2020, 1546 anesthetics were performed in children 18 years and under. Of those, 63 were designated as emergent and hence excluded from our analysis. 153 of the total 1483 (9.4%) of nonemergent bookings were canceled or postponed on the day of surgery. This represented a marked decline from our previous year's 13.7% same‐day cancellation rate for pediatric patients. The most common reason for case cancellations (41.8%) was acute illness. Cancellation rates varied from month to month, with the highest cancellation rate of the year in September 2019 (18.8%). The departments of Podiatry and Gastroenterology represented the highest cancellation rates as a denominator of their case volumes, 15.4% and 15.2%, respectively. Younger children had 2.4 times the odds (95% CI: 1.720, 3.4) of cancellation compared to older children. Discussion: The virtual pediatric perioperative home (VPPH) may benefit quality of care while decreasing costs to pediatric patients, families, and hospital systems. While direct financial gains may be difficult to demonstrate, the VPPH has the potential to reduce OR delays and same day cancellations related to questions of medical optimization. In the context of a socioeconomically disadvantaged patient population, our VPPH's team of subspecialists created inroads for at risk children to establish or reestablish care for their comorbidities, while collaboration with the Department of Children and Families further streamlined communication and consent for pediatric patients in foster care. Conclusions: The authors describe the design and successful implementation of a telemedicine‐based pediatric preanesthesia triage and medical optimization service at a large safety net hospital. By creating a communication network of pediatric subspecialists, the anesthesiologists were able to, at minimal institutional cost, coordinate care for children with a variety of comorbidities leading up to the day of surgery. This yielded a 9.4% same day cancellation rate in a complex, socioeconomically disadvantaged pediatric patient population at a general hospital.